ANALISIS KUALITAS AIR DAN KELUHAN GANGGUAN KULIT PADA MASYARAKAT PENGGUNA AIR SUNGAI SIAK DI PELABUHAN SUNGAI DUKU KELURAHAN TANJUNG RHU KECAMATAN LIMAPULUH KOTA PEKANBARU TAHUN 2012 - Fadillah Ismy; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2013)
Analysis of water quality and skin disorder complaint from water users of Siak river in Duku River Port, Tanjung Rhu village, Limapuluh sub-district Pekanbaru City in 2012. Siak river is one of the biggest river in Pekanbaru City and be a source of water by the society in Tanjung Rhu village. The reduction of water quality in Siak river was caused by the effect of waste disposal from industries activity and domestic waste along the river. The use of polluted water may cause health problem for water users, one of the health problem is related to skin disorder. The aim of this study were to analysis of water quality and skin disorder complaint from water users of Siak river in Duku River Port, Tanjung Rhu village, Limapuluh sub-district Pekanbaru City in 2012. Type of this research was descriptive with the population for 470 persons and the number of sample was 82 persons. Sample taking techniques was done with choice in non-random sampling, namely accidental sampling. The results of the research conducted in the were Siak River by physical parameters, chemistry, and microbiology, show that there three parameters that exceed the water quality standard based on PP. 82 Year 2001 on the Management Quality of Water and Water Pollution Control, the parameters TSS, BOD and COD. The study of 82 respondents, there were 18 respondents (22%) who had complaints of skin disorders. Based on these results, it can be suggested to the government to control the disposal of waste from industries in accordance with applicable regulations, and conduct counseling to communities for do not use the Siak River water until the quality of water meets the health requirements. Keywords : Water Quality, Skin Health Disorder